DAMPAK NEGATIF GAWAI DALAM KEGIATAN BELAJAR ANAK DI RUMAH KELAS 4 SD DIPERUMAHAN INDAH SARI KELURAHAN REJOSARI KECAMATAN TENAYAN RAYA KOTA PEKANBARU (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstrak: This study examines the Negative Impact of Gawai in Learning Activities of Children in Class 4 Primary Schools in Indah Sari Housing, Rejosari Sub-District, Tenayan Raya District, Pekanbaru City. This study uses discuss qualitative descriptive paradigm. Research subjects will be determined based on purposive sampling, there are 2 (two) informants in this study. Data collection is done by way of collection (collection), documentation, in-depth interviews (indept interviews), data analysis is done by: data reduction (data reduction); data presentation (data display); and approves conclusions and verification (drawing conclusions / verification). The results showed: 1) The Negative Impact of the Device in Children Learning Activities at Home, from the negative indicator of the device as an action / implementation that has been carried out, 2) the supporting factors of the negative influence of this device on the interaction with the family around. availability of facilities and infrastructure., 3) The Negative Impact of the Device in the Learning Activities of Children in Class 4 Homes at Dipe Perumahan Indah Sari, Rejosari Village, Tenayan Raya District, Pekanbaru City, lack of development, brain development becomes less optimal and can be used to improve with people, such as parents who the main and the people around the neighborhood.Key Words: Negative Effects of Devices and Learning for Children